Direct and indirect effects of heatwaves on a coral reef fishery. (19th December 2020) - Brown, Christopher J.; Mellin, Camille; Edgar, Graham J.; Campbell, Max D.; Stuart‐Smith, Rick D.
Abstract: Marine heatwaves are increasing in frequency and intensity, and indirectly impacting coral reef fisheries through bleaching‐induced degradation of live coral habitats. Marine heatwaves also affect fish metabolism and catchability, but such direct effects of elevated temperatures on reef fisheries are largely unknown. We investigated direct and indirect effects of the devastating 2016 marine heatwave on the largest reef fishery operating along the Great Barrier Reef (GBR). We used a combination of fishery‐independent underwater census data on coral trout biomass ( Plectropomus and Variola spp.) and catch‐per‐unit‐effort (CPUE) data from the commercial fishery to evaluate changes in the fishery resulting from the 2016 heatwave. The heatwave caused widespread, yet locally patchy, declines in coral cover, but we observed little effect of local coral loss on coral trout biomass. Instead, a pattern of decreasing biomass at northern sites and stable or increasing biomass at southern sites suggested a direct response of populations to the heatwave. Analysis of the fishery‐independent data and CPUE found that in‐water coral trout biomass estimates were positively related to CPUE, and that coral trout catch rates increased with warmer temperatures. Temperature effects on catch rates were consistent with the thermal affinities of the multiple species contributing to this fishery. Scaling‐up the effect of temperature on coral trout catch rates across the region suggests that GBR‐wide catches were 18% higher for a given level of effort during the heatwave year relative to catch rates under the mean temperatures in the preceding 6 years. These results highlight a potentially large effect of heatwaves on catch rates of reef fishes, independent of changes in reef habitats, that can add substantial uncertainty to estimates of stock trends inferred from fishery‐dependent (CPUE) data. Overestimation of CPUE could initiate declines in reef fisheries that are currently fully exploited, and threaten sustainable management of reef stocks. Abstract : Marine heatwaves are increasing in frequency and intensity, and indirectly impacting coral reef fisheries. We investigated direct and indirect effects of the devastating 2016 marine heatwave on the largest reef fishery operating along the Great Barrier Reef. We found warming increased the susceptibility of coral trout to being caught by a line fishery. Scaling‐up the effect of temperature on coral trout catch rates across the region suggested that the heatwave raised catches by 18% above normal. We suggest heatwaves have implications for the management of coral trout and other reef fisheries globally.